A Unique Case of Diffuse Histiocytic Proliferations Mimicking Metastatic Clear Cell Carcinoma in the Hydrocele Sac - Chandanwale, Shirish S; Vimal, Shruti S; Rajpal, Mohit; Mishra, Neha (Journal of Laboratory Physicians, 2014)
Reactive histiocytic proliferations are extremely rare in paratesticular structures. Nodular histiocytic proliferations have been described in mesothelial-lined locations and only at few nonmesothelial sites. Diffuse histiocytic proliferations are described only in the pelvic peritoneum. We report the first case of diffuse histiocytic proliferation in the hydrocele sac of a 45-year-old man. Predominant histiocytes showed clear cytoplasm and signet ring-like change. Mucicarmin stain did not demonstrate mucin in the cytoplasm. Immunohistochemistry (IHC) staining showed nonspecific staining of these cells with carcinoembryonic antigen and negative staining with epithelial membrane antigen, pan-Cytokeratin, calretinin, cytokeratin 7, 20 and prostate-specific antigen. Strong diffuse cytoplasmic positivity for CD68 defined the mononuclear phagocyte nature of these cells. Diffuse histiocytic proliferations can occur in the hydrocele sac. Histochemical and IHC stainings are critical for accurate diagnosis and to avoid unnecessary surgery.
Keywords: Clear cells; diffuse; histiocytes; Immunohistochemistry; signet ring cells